TINJAUAN YURIDIS KEWENANGAN PRESIDEN DALAM PEMBERIAN AMNESTI DAN IMPLIKASINYA TERHADAP PEMENUHAN HAK ASASI MANUSIA - Mallongi, Andi Agung; Ryan Ramdani; Rabbisulyani; Yoga Saputra (Kantor Wilayah Kementerian Hukum Daerah Istimewa Yogyakarta, 2025)
Abstract The development of information and communication technology has increased the urgency of protecting personal data in Indonesia, especially with the rise in data breach incidents that affect citizens’ privacy rights. This study aims to identify human rights violations that occurred in the National Data Center data breach in 2024 and describe the impacts experienced by the Indonesian public as a result of the incident. Using a qualitative approach, this study collects data through literature review related to data breach cases and human rights in Indonesia. The study results show that: 1) The identification of human rights violations in the 2024 national data breach is a violation of citizens’ privacy rights and a violation of human rights concerning personal data protection. 2) The data breach has a direct impact on privacy rights and increases the risk of fraud and identity theft. Additionally, the data breach also disrupts essential public services, such as the tax system, immigration services, and education. This study recommends improvements to legal policies and increasing public awareness of the importance of data privacy. The findings are expected to contribute to strengthening data protection regulations in Indonesia, as well as promoting improved cybersecurity and government accountability in safeguarding citizens’ personal data.